(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study was to analyze the influence of leadership, principal management, and interpersonal communication on the performance of elementary school teachers in Montasik sub-district. The success of national education goals depends on the human resources in the school, namely principals, teachers, operators, administration, school guards, and students. This research was conducted with a quantitative approach. Data collection techniques using questionnaire dissemination techniques and analyzed using the help of SPSS Windows Version 21 Software and tendency tables of research variables. This research was conducted in elementary schools in Montasik sub-district consisting of 5 schools, namely SDN Pante Kareung, SDN Piyeung, SDN 1 Lampaseh, SDN 2 Lampaseh and SDN Semet. This research was conducted using a quantitative approach. The results of this research prove that principal leadership, principal management and interpersonal communication tested using multiple linear regression together have a positive and significant effect on the performance of elementary school teachers in Montasik District, 47.50%.